An Analysis of the Micropropagation and Peculiarities of Eggplant (Solanum melongena L.) Cultivation Technology - Tucuser , Yana; Pyshnaya, Olga; Shafigullin, Damir; Soldatenko, Alexey (KnE Life Sciences, 2021)
This review is devoted to biotechnological methods and approaches used in eggplant selection. Using in-vitro techniques, micropropagation makes it possible to obtain Solanum melongena L. plants identical to the original ones. This article discusses various aspects of eggplant microcloning; draws conclusions about the successful induction of shoots, which is an important stage required for the regeneration of the callus; and describes the methodological issues of origin, explant treatment, cultivation features, composition of nutrient media, growth regulators, growing conditions and rooting algorithms, and adaptation of the resulting regenerant plants. The microclonal reproduction of Solanum melongena L. by organogenesis from cotyledon and hypocotyl explants is described. After explants were introduced into an in-vitro culture, significant differences in the nature of growth and development of the tissues in the nutrient media were observed on the 6-8th day. A comparative analysis of the stimulating effect of growth regulators revealed that thidiazuron with a concentration of 0.02 mg/l had the highest efficiency; its effect on the regenerative capacity of the explant depended on the concentration in the medium. The dependence of all stages of microclonal reproduction on the genotype is shown. Keywords: Solanum melongena L., eggplant, nightshade, microcloning, biotechnology